Chained fuzzy modules - Semeein, S. B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Let R be a commutative ring with unity. In this paper we introduce the notion of chained fuzzy modules as a generalization of chained modules. We investigate several characterizations and properties of this concept